2020
DOI: 10.1186/s12894-020-00766-4
|View full text |Cite
|
Sign up to set email alerts
|

Impact of maintenance therapy using a half dose of the bacillus Calmette–Guérin Tokyo strain on recurrence of intermediate and high-risk nonmuscle invasive bladder cancer: a retrospective single-center study

Abstract: Background Data are scarce regarding intravesical maintenance therapy (MT) with the low-dose bacillus Calmette–Guérin (BCG) Tokyo strain. We investigated the efficacy and safety of MT with a half dose of the Tokyo strain for patients following transurethral resection of nonmuscle invasive bladder cancer (NMIBC). Methods This study retrospectively reviewed clinical data on 78 patients diagnosed with intermediate or high-risk NMIBC followed by either… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 32 publications
1
10
0
1
Order By: Relevance
“…The characteristics and recurrence rates described in the 19 included studies are shown in Table 1 [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. These eligible studies were published between 1987 and 2021.…”
Section: Characteristics Of Included Studies With Quality Assessment ...mentioning
confidence: 99%
“…The characteristics and recurrence rates described in the 19 included studies are shown in Table 1 [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. These eligible studies were published between 1987 and 2021.…”
Section: Characteristics Of Included Studies With Quality Assessment ...mentioning
confidence: 99%
“…Because in the KURG study, the number of maintenance instillations was reduced from three to two, patients tolerated BCG treatment well, and the completion rates were high during the 3 years of treatment, with cancer control rates comparable to other reports [20, 23]. Koguchi et al [24] reported that maintenance therapy with the low-dose BCG Tokyo-172 strain (40 mg) showed acceptable efficacy and safety on the same schedule as the KURG study. In our study, we excluded patients who received BCG maintenance therapy and examined only those who received BCG induction therapy because the BCG maintenance therapy schedule was different for each institution.…”
Section: Discussionmentioning
confidence: 70%
“…Sixty-two studies [ 2 , 3 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76...…”
Section: Resultsunclassified
“…The vast majority of the studies (n = 34, [ 24 , 25 , 26 , 27 , 28 , 29 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 48 , 50 , 51 , 53 , 55 , 56 , 60 , 62 , 63 , 65 , 68 , 69 , 71 , 75 , 76 , 77 , 79 , 80 , 81 ]) were single-arm with no direct comparison across other strains. On the contrary, the remaining n = 27 [ 2 , 3 , 23 , 30 , 31 , 32 , 33 , 43 , 44 , 45 , 47 , 49 , 52 , 54 , 57 , 58 , 59 , 61 , 64 , 66 , …”
Section: Resultsmentioning
confidence: 99%